Fungal Co-infections and COVID-19: A Global Overview of Regional Trends, Risk Factors and Response Strategies - Mphande, Fingani Annie (My University, 2025)
Fungal infections are one of the important but often neglected infections in humans with distribution worldwide. Approximately 1 in 8 individuals globally are affected by fungal diseases. A global increase in fungal co-infections has been reported in several regions between 1990 and 2021. Fungal infections affect the health, livelihood and quality of life with approximately 66.7% disability adjusted life years (DALYs) with a standardized DALY of 7789.55 per 100,000 population. Apart from cutaneous infections, a more severe and often fatal form of fungal disease is invasive fungal infections (IFI). These IFIs affect various organs with the ability to spread to other parts of the body. Aspergillus spp., Mucor spp., Rhizopus spp. and Candida spp. were the most common species reported with increased morbidity and mortality observed in severely ill patients during the COVID-19 pandemic. Current diagnostic approaches remain a challenge especially in limited resource settings affecting accurate diagnosis and timely treatment. This chapter will focus on fungal infections reported during and after the COVID-19 pandemic in all the WHO regions. Associated underlying diseases, treatment and response will also be discussed. The chapter will also explore policies on fungal infection prevention and control and their implementation globally. Strategies including optimal diagnostic approaches, routine screening and timely initiation of antifungal therapy will be analyzed.
Keywords: Candida auris; COVID-19; COVID-19 Associated Candidiasis (CAC); COVID-19 Associated Mucormycosis (CAM); COVID-19 Associated Pulmonary Aspergillosis (CAPA); Fungal infections; Pneumocystis jirovecii